Focusing on protective factors, resilience and thriving to reduce health disparities and treatment inequities. (2nd January 2022) - Field, Craig; Reingle Gonzalez, Jennifer
ABSTRACT: This special issue seeks to characterize the current state of the science regarding risk and protective factors influencing resilience and thriving in relation to substance use among ethnic minorities and other underserved populations. This epilogue examines the scope of work presented in this special issue, the added value of the research presented herein, and how it can inform future research directions. Health disparities research can be conducted using two key approaches: 1) documenting between-group differences comparing ethnic/racial minorities groups and majority populations; or, 2) documenting within-group differences in a single racial or ethnic group. While characterization of between-group differences is useful to identify existing health disparities, it is essential to understand within-group diversity to fully address these inequities. Studies in this special issue identifying between- group differences focus on resiliency characteristics that could be present across all racial and ethnic groups. The studies examining within-group differences included in this special issue examine novel factors that influence resilience of protective health behaviors. Overall, this special issue examines several potential protective factors in the context of health promoting behaviors related to substance use using a wide range of research methodologies. While it is not exhaustive in its representation of all underserved populations experiencing health disparities and treatment inequities, this special issue includes a broad array of populations from various racial, ethnic, and national groups. Although we have to adequately explore thriving, the current special issue establishes a firm foundation for research on resilience that may extend to thriving.